Tinjauan Hukum Hak Beli Kembali dalam Perjanjian Jual Beli Saham di Pasar Modal - Putra Umbu Sangera; I Nyoman Puru Budiartha; Ni Gusti Ketut Sri Astiti (Jurnal Preferensi Hukum, 2021)
A repurchase right agreement is a form of agreement that occurs and is found in people lives, such as residents who can take back their goods that have been sold under certain provisions as set out in article 1519 of the Civil Code. The aim of this research was to determine the legal review of the right to buy back in the share sale and purchase agreement in the capital market. The type of research used is normative with statutory approach. The source of legal material in this research is primary such as positive normative legal theory which stands on the doctrine that law is identical to pure norms in an objective sense free from ideological, ethical, and sociological values. The technique of legal materials used is by reading and quoting by analyzing willing invitations and using small notes taken from books, literature, and other sources related to the issues discussed. The data that has been obtained are then analyzed and analyzed qualitatively. The result shows that the rights and obligations of the parties who sell shares in the capital market must be equal and fair, before the rights and obligations are equal, fair, and implemented, they must first make an agreement. Legal remedies that can be taken if a contract error occurs can be made through external courts (non-litigation) and courts (litigation).